2019
DOI: 10.1016/j.jalgebra.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Powerfully nilpotent groups

Abstract: We introduce a special class of powerful p-groups that we call powerfully nilpotent groups that are finite p-groups that possess a central series of a special kind. To these we can attach the notion of a powerful nilpotence class that leads naturally to a classification in terms of an 'ancestry tree' and powerful coclass. We show that there are finitely many powerfully nilpotent p-groups of each given powerful coclass and develop some general theory for this class of groups. We also determine the growth of pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 6 publications
(7 reference statements)
0
28
0
Order By: Relevance
“…Now the possible types for non-abelian groups of rank greater than 2 are (1, 1, 1, 1, 2), (1, 1, 1, 3), (1, 1, 2, 2), (1,1,4), (1,2,3) and (2,2,2). Those that are not covered by the general examples above are (2, 2, 2), (1,2,3) and (1,1,2,2). Let G be a group of type (2,2,2).…”
Section: The Case When P Is Oddmentioning
confidence: 99%
See 2 more Smart Citations
“…Now the possible types for non-abelian groups of rank greater than 2 are (1, 1, 1, 1, 2), (1, 1, 1, 3), (1, 1, 2, 2), (1,1,4), (1,2,3) and (2,2,2). Those that are not covered by the general examples above are (2, 2, 2), (1,2,3) and (1,1,2,2). Let G be a group of type (2,2,2).…”
Section: The Case When P Is Oddmentioning
confidence: 99%
“…, a r such that G = a 1 · · · a r and such that |G| = o(a 1 ) · · · o(a r ). In [3,Theorem 2.7] we furthermore showed that the generators can be chosen such that the following chain is powerfully central G ≥ a p 1 , a 2 , . .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conjectured in [6] that the bound given in (b) is attained and we will show in this paper that this is the case when p > r . A powerfully nilpotent group, for which this bound is attained, will be called a group of maximal powerful class.…”
mentioning
confidence: 71%
“…Theorem [6] Let G be a powerfully nilpotent group of rank r ≥ 2 that has a maximal tail. Suppose G has order p n , powerful class c and exponent p e .…”
mentioning
confidence: 99%